Management of Accidental and Iatrogenic Foreign Body Injuries to Heart- Case Series - Kumar, Rupesh (J Clin Diagn Res, 2017)
Accidental and iatrogenic foreign body injuries to heart require immediate attention and its timely management is cornerstone to the life of an individual. We describe in detail five cases of Accidental and iatrogenic foreign body injuries to heart encountered between January 2013 and July 2016. Our series included the following: needle stick injury to the right atrium (1 case) retained catheter fragments in the distal main pulmonary artery (1 case), right ventricle injury during catheterisation study (1 case), right ventricle injury during permanent pacemaker lead placement (1 case), device migration in atrial septal defect closure (1 case). Foreign bodies were removed from the cardiac cavities when the patient presented with features of infection (1 case), cardiac tamponade (2 case), anxiety (1 case), and haemodynamic instability (1 case). The management of accidental and iatrogenic foreign body injuries to heart requires immediate attention. Foreign bodies in the heart should be removed irrespective of their location and symptomatology. Asymptomatic foreign bodies diagnosed immediately after the injury with associated risk factors should be removed; asymptomatic foreign bodies without associated risks factors or diagnosed accidentally after the injury also need surgical intervention to allay fears of anxiety in patient and their relatives, to prevent any late complications and also for medico-legal purpose.